Patient navigation: fighting for the rights of breast cancer patients in Brazil - Gioia, Sandra; Brigagão, Lucia; Rocha, Maicon; Goss, Paul (Mastology, 2021)
Introduction: The content of this article deals with the experience of the navigation program for patients in a breast cancer diagnosis center of the State Health Department of Rio de Janeiro. The objective was to show how the patient navigation program can allow the proper application of the 60-day Law, being a topic of interest for the planning and evaluation of actions to control this cancer in Brazil. Methodology: The patient navigator accompanied women from the Unified Health System (Sistema Único de Saúde — SUS) with a diagnosis of breast cancer to start treatment at a specialized center within 60 days. Information on the clinical characteristics of the patients, clinical dates and barriers encountered were collected. Univariate logistic regression was used to assess factors associated with starting treatment within 60 days. Results: From January to July 2020, 301 breast biopsies were performed, 126 (42%) of breast cancer. The mean age was 54 years (26–88). 75% of the lesions were diagnosed in advanced stages (IIB to IV). The mean time to start treatment was 39 days (11–108). The main barriers found were: fear (93%), difficulty in communicating with the medical team (81%), uncoordinated health care (37%). Being treated outside the city of Rio de Janeiro (RJ) was the main factor associated with treatment within 60 days (79.5% vs. 20.5%, p < 0.001). Conclusion: The integration of the patient browser into work processes contributed to compliance with the 60-day Law in 86% of cases. In the context of a complex and fragmented healthcare system for a population in a situation of socioeconomic vulnerability, the patient navigation program proves to be a tool to increase the rate of law enforcement in Brazil.